Psychosocial impact of acne and postinflammatory hyperpigmentation - Katlein França; Jonette Keri (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Acne is one of the most common skin diseases. It has significant effect on self-image and negative impact on quality of life. Postinflammatory hyperpigmentation is an acquired hypermelanosis that occurs after a skin injury or cutaneous inflammation. It is common sequelae in acne patients. Objectives: This study aimed to investigate the psychosocial impact of acne and postinflammatory hyperpigmentation among patients treated in a dermatology outpatient clinic at the University of Miami Hospital. Methods: The study had the participation of 50 patients with acne and postinflammatory hyperpigmentation. All participants volunteered to complete an anonymous questionnaire containing socio-demographical information, questions about patient's attitudes toward postinflammatory hyperpigmentation caused by acne, the Cardiff Acne Disability Index and the Dermatology Life Quality Index. Results: Postinflammatory hyperpigmentation was more predominant in the face. Makeup was frequently used to conceal the imperfections and the majority of patients felt embarrassed due to their condition. Interestingly, the majority of our patients did not have their quality of life impacted for acne and postinflammatory hyperpigmentation. Study limitations: A limitation of the study was the relatively small sample size. For this reason, the findings of the study should not be generalized to the broader community. Conclusion: The current medical literature has many studies analyzing the psychological impact of acne. This study is the first study in the literature that analyzed the psychosocial impact of acne and postinflammatory hyperpigmentation caused by acne.